Peran Guru Bimbingan dan Konseling dalam Mengatasi Kecenderungan Perilaku Agresif Peserta Didik di MAN Asahan - Miftahur Rahmi Sitompul; Purbatua Manurung (Mu'allim, 2023)
Aggressive behavior is behavior carried out by individuals or groups that is intended to hurt, injure, and harm other people, both individuals and groups, with intention or on purpose, both verbally and nonverbally. The aims of this study were (1) to describe the factors that cause students to behave aggressively at MAN Asahan, (2) to describe the role of the counseling teacher in dealing with the aggressive behavior of students at MAN Asahan. This study uses a qualitative descriptive research method. The subjects and objects in the study were guidance and counseling teachers and students. Research instruments are interviews, observation and documentation. The results of the study show that (1) the causes of aggressive student behavior are largely due to the hard character of students and tend to assume that the behavior they are doing is normal and due to a lack of supervision, attention and affection from parents so that children tend to feel they can do anything desired and (2) the role of the guidance and counseling teacher in reducing the aggressive behavior of students is quite good, namely by investigating the student's problems. As well as carrying out counseling services, in the form of: individual counseling services, group counseling services, etc.